2010
DOI: 10.3748/wjg.v16.i6.740
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiocentesis with cisplatin for malignant pericardial effusion and tamponade

Abstract: Pericardiocentesis along with catheter drainage appears to be a safe and effective for pericardial malignant effusion and tamponade, and cisplatin instillation prevents recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
2
11
0
6
Order By: Relevance
“…All patients achieved obvious and sustained symptom remission, and six of the seven patients did not suffer from effusion recurrence before death. Similar studies using intrapericardial cisplatin reported median survival times of 84 ± 39 days [30] and 120 ± 71 days (range, 68–268 days) [31]. Our results in this group of patients suggest that intrapericardial BEV may be more effective than other therapies in treating MPCE.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…All patients achieved obvious and sustained symptom remission, and six of the seven patients did not suffer from effusion recurrence before death. Similar studies using intrapericardial cisplatin reported median survival times of 84 ± 39 days [30] and 120 ± 71 days (range, 68–268 days) [31]. Our results in this group of patients suggest that intrapericardial BEV may be more effective than other therapies in treating MPCE.…”
Section: Discussionsupporting
confidence: 78%
“…Maisch et al [30] and Oida et al [31] reported nausea in most patients who received cisplatin infusions. In contrast, no hematological toxicity, hepatotoxicity, or nephrotoxicity was observed in any of the patients in our study after BEV treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Cisplatin is the most common agent for treating malignant effusion because of its high patient response rate; however, it is associated with common chemotherapeutic adverse events. 6 Chen et al reported a complete remission rate of 71.4% in non-small-cell lung cancer (NSCLC) patients treated with etoposide and cisplatin by pericardial perfusion to alleviate MPCE. 7 However, the authors also reported MPCE recurrence and gastrointestinal and hematological toxicities in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several chemotherapeutic agents have been used for this scope, but the most used are platinum and triethylenethiophosphoramide (thiotepa), an anticancer agent with sclerosing properties. Intrapericardial cis-platinum or carboplatinum, with different schedules (10 mg over 5 continuous days, 10 mg over 3 days, 30 or 50 mg in single injection) has been used for 30 years with good results in various tumors, mostly in lung cancer pericarditis [60][61][62][63][64][65][66][67][68]. In a study on nine patients with various tumors, Tomkowski had two long-lasting responses, but most of the patients died of cancer within 3 months, and in all of the seven patients who had an autopsy, neoplastic pericardial involvement was found even without pericardial effusion [62].…”
Section: Antineoplastic Treatmentsmentioning
confidence: 99%